Menstrual Cycle Abnormalities in Patients with Prolactinoma and Drug-induced Hyperprolactinemia - Kulshreshtha, Bindu (Indian J Endocrinol Metab, 2017)
BACKGROUND AND OBJECTIVE: Hyperprolactinemia affects the reproductive endocrine axis; however, the degree of dysfunction may vary depending on etiology. The aim of the present study was to analyze menstrual cyclicity in patients with prolactinoma and drug-induced hyperprolactinemia (DIH). METHODOLOGY: Patients with prolactinoma and DIH were retrospectively analyzed for menstrual cyclicity at presentation and response to therapy. RESULTS: Of 128 females with hyperprolactinemia, 58 had prolactinoma (41 microadenoma and 17 macroadenoma) and 39 had DIH. Patients with prolactinoma had higher prolactin levels and increased frequency of oligomenorrhea (77.5% vs. 46%) as compared to DIH. Patients with macroprolactinoma had more severe menstrual disturbances compared to microprolactinoma. A higher percentage of patients with microprolactinoma and DIH achieved regular menstrual cycles compared to macroprolactinoma postcabergoline treatment (85% and 90% vs. 65%). There was no correlation between time to regularization of menstrual cycles with age, menstrual cycle length, duration of menstrual irregularity, or initial prolactin level in patients with prolactinoma. Linear regression analysis showed a significant association between time to regularization of menstrual cycles with time to normalization of prolactin levels (P = 0.001). CONCLUSION: There is a prompt restoration of menstrual cycles in patients with microprolactinoma and DIH. Patients with macroprolactinoma have more severe menstrual disturbances and lesser frequency of cycle restoration postcabergoline treatment compared to microprolactinoma and DIH.